Application of Timber Legality Verification System (SVLK) Policy as Ecolabel Implementation in the Indonesian Timber Industry - Arifin Ma’ruf (Lembaga Contrarius Indonesia, 2021)
Ecolabel is an international environmental standard that has been set by the World Trade Organization (WTO). The application of ecolabel is expected to be a solution for environmental problems. Ecolabeling is carried out with an approach of internationally agreed standards. In the timber industry in Indonesia, ecolabeling is implemented with the Timber Legality Verification System (SVLK) policy. This policy is proven to overcome illegal logging and illegal trade and improve forest governance.Keywords: Ecolabel; SVLK; and Environment.